African Culture a Mixed Bag: An Aesthetic Appreciation of Divine Religion in Refinement of African Cultures - Hashimi, A. O. (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
Culture is an important aspect of African communities, a pivot for sincere development, a mode of existence and an aspect of man’s existential experiences. Without culture there can be no society and without society there can be no humanity. African culture has passed through different stages of evolution from the earliest period to the contemporary time. What constitutes culture in Africa today is embedded with many alien ideas and erosion of values. Therefore, in the quest for achieving the fundamental mission of placing Africa contemporary globalized world, African culture needs an ethical overhaul in separating it from accretions? Therefore this paper examines the conditions of African people with particular focus on the forceful influences of colonialism on African culture. The paper employs analytical research method. The paper argues that there is a need of belief in the importance of divine religion and relevance of God to human existence for improving human existential conditions. Hence, the guidance of God is a source of light to African tunnel. Keywords: Africa, Culture, Mixed bag, Divine religion and Refinement